Methyl- and phenylmercury(II) derivatives of 2-mercaptobenzothiazole. Crystal structure of (2-mercaptobenzothiazolato)methylmercury(II) - Bravo, Jorge; Casas, José S.; Castaño, María V.; Gayoso, Miguel; Mascarenhas, Yvonne P.; Sánchez, Agustín; Santos, Carlos de O. P. [UNESP]; Sordo, J. (My University, 1985)
The complexes MeHgL and PhHgL (HL = 2-mercaptobenzothiazole) have been obtained from the reaction of the ligand with methylmercury hydroxide and phenylmercury acetate, respectively, in methanol. MeHgL, which has been characterized by single-crystal X-ray diffraction analysis (crystal data: triclinic, space group P1, with a = 8.009 (4) Å, b = 10.042 (4) Å, c = 13.074 (3) Å, α = 101.25 (2)°, β = 102.61(3)°, γ = 101.42 (3)°, R = 0.067), crystallizes with two independent molecules, I and I′, contained in each asymmetric unit with a coordination geometry based on the almost linear C-Hg-S group (Hg-S = 2.369 (6) Å, Hg-C = 2.06 (2) Å, and C-Hg-S = 177.7 (7)° for I; Hg-S = 2.375 (6) Å, Hg-C = 2.10 (3) Å, and C-Hg-S = 178.8 (6)° for I′). A secondary intramolecular interaction between the mercury atom and the C=N group of the ring and some weak intermolecular interactions between the metal and sulfur atoms were also found. The vibrational spectra of this compound and the phenylmercury(II) compound are discussed in light of the crystal structure. Diagnostic criteria of the bonding modes for the ligand are assessed. © 1985 American Chemical Society.